Quantifying the Resilience of the U.S. Domestic Aviation Network During the COVID-19 Pandemic - Bauranov, Aleksandar; Parks, Steven; Jiang, Xuan; Rakas, Jasenka; González, Marta C. (Frontiers in Built Environment, 2021)
This paper analyzes the impacts of COVID-19 pandemic on the United States air transportation network between March and August 2020. Despite dramatic reductions in flight and passenger volumes, the network remained robust and resilient against perturbation. Although 24% of airports closed, the reduction in network efficiency was only 5.1%, which means airlines continued to serve most destinations. A deeper analysis of airport closures reveals that 1) small peripheral airports were the most likely to be closed; 2) socio-economic and epidemiological factors characterizing the airport’s region such as income, income inequality, political leaning, and the number of observed COVID cases were not predictive of airport closure. Finally, we show that high network robustness has a downside: although emissions from United States air traffic in 2020 fell by 37.4% compared to 2019, mostly due to the drop in the number of flights, emissions per passenger doubled in the period April to August 2020 and increased eightfold in the week of April 5–11. This rise indicates inefficient use of resources by airlines.